Pendampingan Sosialisasi dan Pelatihan Melalui Padat Karya Tunai (PKT) dengan PPK 4.3 Provinsi Jawa Timur Untuk Meningkatkan Perekonomian Masyarakat Wilayah Sadang Kabupaten Gresik - Triwahyudi, Yoki; Yulianis, M. Sifa Fauzi; Renggana, Yunus (Bisma : Bimbingan Swadaya Masyarakat, 2023)
Padat Karya Tunai is a government program in the form of village community empowerment activities, especially the poor and marginalized, are productive in nature that prioritize the use of local resources, labor, and technology to increase income, reduce poverty and improve people's welfare. Through training Padat Karya Tunai, This mentoring activity is able to open new jobs for the community, so that there is economic equality to rural areas as well as to overcome inequality